Ultrasonographic measurements of the inferior vena cava diameter in newborns: is it a useful tool for choosing an umbilical venous catheter? - Galdo, Francesca; Trappan, Antonella; Cossovel, Francesca; Rodriguez-Perez, Carmen; Ronfani, Luca; Montaldo, Paolo; Bibalo, Cristina; Travan, Laura; Risso, Francesco Maria (Frontiers in Pediatrics, 2023)
The primary outcomes of this study were to evaluate the diameters of the Inferior Vena Cava (IVC) in a cohort of newborns and the correlation between newborn weight and IVC diameter. The secondary outcome was to evaluate the concordance between the measures carried out by the two investigators. Methods: Two blind examiners performed ultrasound (US) evaluation of the diameter of IVC in neonates with a weight ranging from 2 kg to 4 kg. Exclusion criteria included hemodynamic instability, known vascular malformations and major congenital malformations. Results: A total of 143 neonates were enrolled from June 2019 to January 2021. All the US examinations were performed in the first 3 days of life. After dividing the patients into the 2 groups according to their weight at the time of examination (2,0-2,99 kg and 3,0-4,0 kg), IVC median diameter measured by examiner 1 was 3.1 mm (interquartile range 2.8-3.4) and 3.4 mm (interquartile range 2.9-3.8) respectively for the 2 groups (p=0.003), and IVC median diameter measured by examiner 2 was 3.1 mm (interquartile range 2.6-3.3) and 3.3 mm (interquartile range 2.8-3.8) respectively for the 2 groups (p=0.004). The intraclass correlation coefficient was 0.93 (95% CI 0.90-0.95). Conclusion: IVC diameter values varied widely from 1.2 mm to 5.2 mm in newborns with a weight from 2 to 4 kg, and a low correlation between newborn weight and IVC was found, so measuring IVC may be a recommended step prior to insert a Umbilical Venous Catheters (UVC). The between operators' concordance was good. We contemplated IVC diameter could be a potential useful tool to identify the most appropriate UVC, thus trying to reduce the risk of catheter-related thrombosis.